Cytosine-substituted metalloporphyrins: receptors for recognition of nucleotides in ion-selective electrodes - Král, Vladimír; Shishkanova, Tatiana V; Sessler, Jonathan L; Brown, Christopher T (Organic & biomolecular chemistry, 2004)
A new series of cytosine-substituted metalloporphyrin conjugates (containing Co(II) and Zn(II) as the coordinated metals) were designed and investigated as nucleotide receptors in PVC-membrane-based ion-selective electrodes under neutral conditions. The potentiometric results indicate that these systems, in particular the Co(II)-containing complex, may be potentially useful sensors for complementary nucleotide substrates in the presence of 10 mol% tridodecylmethylammonium chloride (K(Pot.)(5'-GMP/5'-AMP)= 0.045).
Keywords: Electrodes; Cytosine; Biosensing Techniques; Potentiometry; elektrody; potenciometrie; biosenzitivní techniky; nukleotidy; molekulární struktura; Nucleotides; metaloporfyriny; Molecular Structure; polyvinylchlorid; cytosin; Metalloporphyrins; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; ionty; Ions; Polyvinyl Chloride